Heterogeneous preferences and the effects of incentives in promoting conservation agriculture in Malawi - Ward, Patrick S.; Bell, Andrew R.; Parkhurst, Gregory M.; Droppelmann, Klaus; Mapemba, Lawrence (International Food Policy Research Institute, 2015)
Malawi faces significant challenges in meeting its future food security needs because there is little scope for increasing production by simply expanding the area under cultivation. One potential alternative for sustainably intensifying agricultural production is by means of conservation agriculture (CA), which improves soil quality through a suite of farming practices that reduce soil disturbance, increase soil cover via retained crop residues, and increase crop diversification. We use discrete choice experiments to study farmers’ preferences for these different CA practices and assess willingness to adopt CA. Our results indicate that, despite many benefits, some farmers are not willing to adopt CA without receiving subsidies, and current farm-level practices significantly influence willingness to adopt the full CA package. Providing subsidies, however, can create perverse incentives. Subsidies may increase the adoption of intercropping and residue mulching, but adoption of these practices may crowd out adoption of zero tillage, leading to partial compliance. Further, exposure to various risks such as flooding and insect infestations often constrains adoption. Rather than designing subsidies or voucher programs to increase CA adoption, it may be important to tailor insurance policies to address the new risks brought about by CA adoption.